Leiomyoma Cutis : A Report Of Two Cases - Kumar Hemanth; Kumar Vijay; Thappa Devinder Mohan (Wolters Kluwer Medknow Publications, 1998)
The cass of multiple leiomyoma cutis, an uncommon tumour of the skin diagnosed by an acronym â€LEND AN EGGâ€ and histopathology, are reported here.